MODERATE ATTITUDE OF THE MUSLIM COMMUNITY OF BEKASI REGENCY AND THE PROBLEM OF THE CONSTRUCTION OF THE MOTHER CHURCH TERESSA CIKARANG - Abdul Jamil Wahab; Takiyudin Takiyudin (Penamas, 2022)
Catholics in Bekasi Regency don’t yet have a permanent and licensed church building, even though the number of Catholics in Bekasi Regency is relatively large, around 12 thousand people. building the Mother Teresa Church in Cikarang did not materialize, although it had been proposed since 2015 with complete requirements according to existing regulations, the Bekasi Regency Government did not issue a permit. Through research with an approach approach, it was found that there are several factors that can be categorized as supporting and inhibiting factors. The inhibiting factor is the unresponsive attitude of the Bekasi Regency Government and discriminatory administrative regulations. Meanwhile, the supporting factor is the moderate attitude of local residents who provide support for the establishment of the church. The delay in building permits for the church has resulted in obstacles in terms of worshiping Catholics and getting proper religious education. The attitude shown by the Bekasi Regency Government has violated the basic rights of Catholics to practice religious worship which are guaranteed in the constitution and statutory regulations.